P261 Frequency of B-cell subsets in infliximab-treated paediatric IBD patients. (25th January 2019) - Schnell, A; Schwarz, B; Wahlbuhl-Becker, M; Allabauer, I; Rechenauer, T; Siebenlist, G; Kaspar, S; Ehrsam, C; Rückel, A; Rascher, W; Hörning, A
Abstract: Background: The role of B cells in IBD is ambiguous, as B cells may have both pathogenic as well as protective functions in IBD. On the one hand, autoreactive B cells may contribute to mucosal inflammation via secretion of autoantibodies. On the other hand, B cell subsets with regulatory properties like transitional B cells are thought to provide an anti-inflammatory milieu by producing IL10 and TGF-β. The aim of the study was to investigate in a first step frequency patterns of B cell subsets in paediatric IBD patients undergoing a treatment with Infliximab (IFX). Methods: The numerical distributions of transitional, naïve and memory B cells as well as antibody-secreting cells like plasmablasts and plasma cells were assessed at initiation of therapy and in the longitudinal course by FACS multi-colour analysis. The study included 9 children with UC and 13 with CD and 9 age-matched healthy controls. Blood samples were obtained at baseline, before fourth infusion at the end of induction phase and after 6 and 12 months under therapy maintenance. With regard to clinical and biochemical remission, we categorised every patient with a faecal calprotectin level below 100 µg/g or a decrease of <10% of the baseline value after 12 months as responder. Results: Compared with healthy controls, FACS analysis revealed significantly low percentages of transitional B cells in UC ( p = 0.001), whereas in CD patients we detected either low or highly increased frequencies of transitional B cells. In addition, frequencies of memory B cells were highly elevated in UC patients in ( p = 0.0357). We also observed highly increased numbers of antibody-secreting B cell subsets in a small number of patients from both entities at the end of induction phase. With regard to therapeutic effects we could show that successful IFX therapy was associated with increased numbers of CD19+ B cells in those patients that reached clinical and biochemical remission. Conclusions: The results of our study suggest an involvement of B cells in the pathogenicity of IBD. Especially the findings in UC patients with high frequencies of antigen-experienced memory B cells in contrast to reduced percentages of transitional B cells point towards a disbalance between pro- and anti-inflammatory elements in paediatric IBD. In CD, our findings within all B cell subsets are more ambiguous, suggesting a rather heterogenous B cell spectrum in CD patients.